Estimated environmental risks of engineered nanomaterials in Gauteng. - Nota, Nomakhwezi Kumbuzile Constance (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MScEng (Process Engineering))--University of Stellenbosch, 2011.